Advanced Excel Essentials - Goldmeier, Jordan (Apress : Imprint: Apress, 2014)
Advanced Excel Essentials is the only book for experienced Excel developers who want to channel their skills into building spreadsheet applications and dashboards. This book starts from the assumption that you are well-versed in Excel and builds on your skills to take them to an advanced level. It provides the building blocks of advanced development and then takes you through the development of your own advanced spreadsheet application. For the seasoned analyst, accountant, financial professional, management consultant, or engineer-this is the book you've been waiting for! Author Jordan Goldmeier builds on a foundation of industry best practices, bringing his own forward-thinking approach to Excel and rich real-world experience, to distill a unique blend of advanced essentials. Among other topics, he covers advanced formula concepts like array formulas and Boolean logic and provides insight into better code and formulas development. He supports that insight by showing you how to build correctly with hands-on examples.